Effective Resistance of Gas Flow in Microchannels. (14th March 2013) - Shan, Xiao-Dong; Wang, Moran
Abstract : The resistance of gas flow in microchannels is higher because of the relatively more importance of interfacial effects at microscale. We studied the effective resistance of gas from the wall interactions, the ends effect, and the rarefication effect quantitatively using the three-dimensional (3D) direct simulation Monte Carlo (DSMC) method. The effective resistance is enhanced by the wall interactions, increasing exponentially as the concerned walls distance decreases. For short microchannels, the ends effects from both inlet and outlet also raise the effective resistance of gas flow in microchannels following a reciprocal exponential relationship with the aspect ratio of length to height. The gas rarefication strengthens the effective resistance enhancement by either the wall interaction effects or the ends effects. This work turns a complicated micromechanical problem into simple available formulae for designs and optimization of microengineering.